Praktik Mestimulasi Perkembangan Motorik Anak Usia Dini Melalui Kegiatan Menempel Dan Menggunting - Ni Putu Chandra Paramis Suary; Ni Kadek Ayu Mawarini; I Gusti Ayu Sukerti; Calista Yun; Ida Bagus Alit Arta Wiguna (IAHN Gde Pudja Mataram, 2022)
Cognitive development is a person's ability to think more complexly in reasoning and problem solving. The usual activities carried out at TK Dwijendra Mataram are cutting and pasting. These activities not only stimulate children's cognitive development but fine motor skills and emotions are also well stimulated. This study uses a qualitative approach with observation techniques, interviews and documentation studies. The results of the study found that in terms of physical development these skills are important for the development of fine motor skills, cutting and pasting activities also aim to train motor skills, hand and eye coordination and concentration for children.